The Effect Of Scout and Sispala Coaching On Student Character Development at Darussalam Pannyangkalang Islamic Senior High School, Gowa Regency - Muhlis Muhlis; Muh. Yunus; Elpisah Elpisah (International Journal of Educational Research, 2026)
This study aimed to examine: (1) the effect of Scout coaching on students’ character development; (2) the effect of SISPALA coaching on students’ character development; and (3) the simultaneous effect of Scout and SISPALA coaching on students’ character development at Darussalam Pannyangkalang Islamic Senior High School, Gowa Regency. This research employed a descriptive correlational quantitative approach with a cross-sectional design. The population consisted of all students actively participating in Scout and SISPALA activities. Using total sampling, 24 students were selected as respondents. Data were collected through questionnaires and documentation and analyzed using simple and multiple linear regression with SPSS. The findings revealed that Scout coaching had a positive and significant effect on students’ character development (t = 4.083, p = 0.000 < 0.05). SISPALA coaching also had a positive and significant effect (t = 2.888, p = 0.009 < 0.05). Simultaneously, Scout and SISPALA coaching significantly affected students’ character development (F = 11.911, p = 0.000 < 0.05). The coefficient of determination (R² = 0.531) indicated that 53.1% of the variance in character development was explained by Scout and SISPALA coaching.